A fracture prevention service reduces further fractures two years after incident minimal trauma fracture. (28th May 2013) - Van der Kallen, John; Giles, Michelle; Cooper, Kerry; Gill, Kerry; Parker, Vicki; Tembo, Agness; Major, Gabor; Ross, Linda; Carter, Jan
Abstract Aim To evaluate the impact of a fracture prevention clinic service on initiation of treatment, continuing treatment and subsequent minimal trauma fractures (MTF). Method Participants were people aged 50 and over, with a minimal trauma fracture presenting to the Emergency Department (ED) in a large tertiary referral hospital in New South Wales, Australia, between February 2007 and March 2009. A cohort of patients who attended a Fracture Prevention Clinic (clinic group) were compared with a cohort who did not attend the clinic (non‐clinic group). A telephone questionnaire was conducted with participants or their carers between December 2010 and April 2011 at least 12 months post‐fracture presentation. Questionnaire items included demographics, fracture types, osteoporosis treatment, recurrent fractures and smoking and dietary habits. Data were compared using chi‐squared test for categorical variables and Student's t‐test or Mann–Whitney U‐test for continuous variables. Results Two hundred and fourteen clinic attendees and 220 non‐clinic attendees were surveyed between 12 and 40 months (mean 24 months) post‐initial fracture. New fracture rates were lower in the clinic group (5.1%) than the non‐clinic group (16.4%, P < 0.001). Treatment rates for bone fragility were higher in the clinic group (81.3%) than in the non‐clinic group (54.1%, P < 0.001) with 66.8% of the clinic group and 34.1% of the non‐clinic group on a bisphosphonate or strontium ranelate at the time of the survey (P < 0.001). Conclusion Patients managed by a fracture prevention clinic service following a MTF have fewer new fractures and are more likely to be on treatment for bone fragility.